Reconfiguration of Active Distribution Networks in order to Reduce the Cost of Operation by Distribution Companies - Sara Haghifam; Mahmoud Reza Haghifam (Majlesi Journal of Electrical Engineering, 2024)
The development and installation of Distributed Generators (DGs) in distribution power networks turned these networks from a passive into active ones in power systems. Proper management and control of these resources can help to improve power quality, and increase security and effectiveness of power networks. The power management of DGs considering their operating cost along with reconfiguration of distribution network can reduced the cost of operation, including cost of energy losses, cost of power purchasing from the upstream network and cost of power generation by dispatchable DGs. In this study a new method is presented for daily reconfiguration of distribution network in presence of dispatchable DGs and renewable DGs in order to reduce the total operating cost of distribution companies. Dynamic modeling of renewable DGs based on uncertainty of their output, switching costs and varying load are considered in this paper. Finally the method has been tested in three stages on 16-Bus IEEE to demonstrate the effectiveness of proposed method.